Linguistic precursors of advanced math growth in first-language and second-language learners. (August 2020) - Kleemans, Tijs; Segers, Eliane
Highlights: We examine the role of linguistic skills in advanced mathematics growth. Basic linguistic skills predicted growth in advanced mathematics via arithmetic. Advanced linguistic skills directly predicted the growth in advanced mathematics. Second-language learners score below first-language learners on advanced mathematics. Linguistic skills matter in advanced mathematics growth regardless of linguistic background. Abstract: Background: Language plays an important role in the development of mathematics. Previous research has shown that both basic and advanced linguistic skills relate to fifth-grade advanced mathematics (i.e., geometry and fractions), but these effects have not yet been investigated longitudinally or in a linguistically diverse population. Aims: The present study first examined the differences between first-language and second-language learners in advanced mathematics. Second, we investigated the extent to which the basic and advanced linguistic skills of first-language and second-language learners directly and indirectly (through arithmetic) predict their growth in advanced mathematics from fifth to sixth grade. Methods and procedures: Participants were 153 first-language and 80 second-language learners from 10 to 12 years of age. Classroom as well as individual measures were administered. Outcomes and results: First, the results showed lower scores for second-language learners on advanced mathematics. Second, for both groups of language learners, basic linguistic skills were found to indirectly predict the growth in advanced mathematics via arithmetic skills, whereas advanced linguistic skills directly predicted the growth in geometry and fractions. Conclusions and implications: These results highlight the general need for opportunities to learn the basic and advanced linguistic skills associated with mathematics over individual native language background.